Mangrove Rehabilitation at Alo Beach (Karakelang Islands, Talaud) Using Propagul of Rhizophora mucronata Lamk - Ady Suryawan (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2017)
This study aimed to know the dynamic of survival rate and growth of Rhizophora mucronata Lamk which planted by using propagules at Alo Beach, Karakelang Island, Talaud. The study was conducted from June 2013 to April 2017, used a complete randomized design with 6 treatments i.e. K1, K2, K3, K4, K5, K6. The amount of propagules in every treatment were 100 pieces each. The parameter observed were characteristic of substrat, survival rate,height and diameter of the plant’s in age of 1.5 months and 48 months. The results showed that treatment had a significant effect on survival rate and growth of Rhizophora mucronata plants. The rehabilitation was categorized as success at 1.5 months old, but it was failed inthe 48 months. Beside waves and tides, low substrat nutrition became the main factor that affect the success of mangrove rehabilitation in Alo Beach.The K5 treatment has the highest survival and growth rate of the plant. The K5 treatment using pnematophore as brace, while planting without brace/K1 has lowest survival and growth rate since months old.Keywords: mangroves, rehabilitation, Rhizophora mucronata, Talaud